Sistem Informasi Kegiatan Sekolah Berbasis Web Di SDN Semolowaru 1 Surabaya - Tjatursari Widiartin; Alffit Nadhifatulloh Ichtiarto; Muhammad Ilham Akbar (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2021)
A dynamic school will definitely have a lot of activity agendas. SDN Semolowaru 1 Surabaya is a school that has various types of academic and non-academic activities. In the implementation of these activities, there are some that sometimes the information does not reach the teacher or students. The Web-Based School Activity Information System was built to help the school socialize the activities to be carried out, the activities will not be constrained due to the lack of participation from teachers and students because they do not know when and where these activities will take place. In addition, some of the achievements obtained will be published, so that the public knows the activities and achievements that have been obtained by the school. This can be a promotion to the community. This system is built using the waterfall methodology, where there are 5 stages, namely the communication stage, planning stage, modeling stage, construction stage, and deployment. The analysis technique and system design used is object-oriented and described using the case tool unified modeling language (UML). The first stage, namely the communication stage is carried out at the practical work location with the method of collecting data from observations and interviews. The second stage, namely the planning stage, is carried out to find functional and non-functional requirements which are described by use case diagrams. The third stage, the modeling stage, will be described with a class diagram. The fourth stage, the construction stage is carried out using the PHP programming language and the MySQL database engine. The fifth stage is testing the application.